Chas. H Tillson, The Ordinances of the City of St. Louis, State of Missouri, Digested and Revised by the Common Council of Said City, in the Years 1860 & 1861: With the Constitution of the United States and the State of Missouri, and the Various Charters of the City of St. Louis Page 513, Image 513 (1861) Misdemeanors, § 8 - (:unkn) unknown (General Publisher, 1861)
Hereafter it shall not be lawful for any person to wear under his clothes, or concealed about his person, any pistol, or colt, or slung-shot, or cross-knuckles, or knuckles of lead, brass, or other metal, or bowie knife, dirk knife, or dirk, or dagger, or any knife resembling a bowie knife, or any other dangerous or deadly weapon, within the city of St. Louis
--
Keywords: CARRY - CONCEALED